Electrochemical characterization of atomic layer deposited Al2O3 coatings on AISI 316L stainless steel. (10th June 2016) - Fedel, M.; Deflorian, F.
Highlights: Amorphous Atomic Layer Deposited (ALD) alumina coatings were applied onto AISI 316L. A different number of deposition cycles was investigated. The evolution of the pre-factor Q of the CPE was related to coating degradation. Long term EIS was found to be complementary to short term electrochemical tests. Abstract: In this work the potential of the Atomic Layer Deposition (ALD) technique to deposit thin and compact ceramic films to shield AISI 316L stainless steel against corrosion is investigated. Al2 O3 films were applied onto mirror polished AISI 316L by means of Atomic Layer Deposition to increase its durability. The effect of a different number of self-terminating gas–surface reactions in the ALD chamber (which lead to different thickness of the deposits) was investigated. The physical properties of the coatings were explored by means of FT-IR exploiting the ATR geometry. The corrosion protection properties of the Al2 O3 deposits were investigated by means of electrochemical techniques such as potentiodynamic curves and electrochemical impedance spectroscopy (EIS). In particular, the electrochemical response of the coated substrate was investigated for prolonged immersion time (up to 1000 hours of continuous immersion) to assess the corrosion resistance of the coatings in this condition. Relatively long term EIS measurements revealed that a monitor of the corrosion protection properties during time provides useful information related to the effective corrosion protection of the coatings, integrating the commonly employed short term test (such as polarization curves and short term EIS) to study ALD ceramic coatings.